العوامل المؤثرة في تطبيق محاسبة عروض التجارة: دراسة ميدانية على صندوق الزّكاة بمدينة مصراتة (Journal of Academic Research, 2026)
This study aims to improve the accounting system for trade goods by analyzing the organizational, human, technical, and legislative factors affecting its implementation. It employs a descriptive-analytical approach to diagnose the current situation of Zakat funds in Libya, particularly the Zakat Fund in Misrata. Personal interviews and questionnaires were used to collect data from fund employees, officials, Zakat payers, and beneficiaries, with the goal of developing a comprehensive understanding of the shortcomings and potential improvements in Zakat accounting for trade goods.The results show that the implementation of Zakat accounting suffers from organizational and administrative challenges that hinder efficiency and accuracy. These challenges include a shortage of qualified personnel in Sharia-compliant accounting, a weak technological infrastructure supporting financial and statistical operations, and a deficiency in current legislation and policies that fail to keep pace with technological advancements and international standards related to Zakat accounting. The study recommended updating the legislative and administrative framework and adopting advanced accounting information systems that enhance transparency and efficiency in calculating and collecting zakat. It also recommended developing specialized human resources in Islamic accounting to improve performance and standardize application methods. Furthermore, the study emphasized the importance of integrating zakat accounting into university curricula and professional training programs for accountants to ensure the sustainability of institutional development within zakat funds.Key words: Zakat, Zakat accounting, trade offerings, Zakat fund, descriptive analytical approach, Libya.